Brief intervention as strategy treatment that improves nutritional adherence in obesity: a pilot study - Karina González-Becerra; Joel O. González-Cantero; Angélica M. Martín-Moreno; Elisa Barrón-Cabrera; Alondra Mora-Jiménez; Erika Martínez-López (Revista Mexicana de Endocrinología, Metabolismo y Nutrición, 2023)
Background: Obesity is a chronic disease with high prevalence worldwide. Objective: To evaluate the use of the Brief Intervention for Treatment Adherence (BITA) strategy for enhancing nutritional adherence to weight loss treatment in subjects with obesity. Materials and methods: A clinical trial of 4-month follow-up. The participants were assigned to a group with or without BITA. The nutritional intervention consisted of a 20% reduction in the total energy expenditure. Results: The use of BITA strategy significantly improved adherence to nutritional counseling in comparison with participants that did not receive BITA (71.8 ± 13.8 versus 42.0 ± 16.8%, p < 0.05). The group BITA showed significant improvements in weight loss (-4.9 ± 4.0 versus 1.3 ± 3.6 kg), body mass index (-1.7 ± 1.3 versus 0.7 ± 2.0 kg/m2), body fat mass (-3.1 ± 4.0 versus 2.3 ± 3.5 kg), and abdominal fat, (-1.1 ± 2.8 versus 1.9 ± 2.2%), compared to group without BITA. Conclusions: The BITA strategy demonstrated to be useful for improving adherence to a nutritional intervention, achieving a greater weight loss.